Population Estimation of Golden Jackal (Canis Aureus) Using Different Methods in Various Habitats of Cachar District, Southern Assam - Debnath, D.; Choudhury, P. (Indian Forester, 2013)
Golden jackal (Canis aureus) is one of the top carnivores distributed in different habitats in Cachar district, Assam (India). Survey was conducted in the three representative habitats of Cachar district, Barak Valley, Assam (India), viz. Reserve Forest, Tea garden and unprotected forests from January to June, 2013 for estimation of minimum population by both direct (sighting) and indirect (howling and active den) survey methods. From the study, more number of jackals were documented by howling survey (n=89), followed by direct sighting (n=22) and active den survey (n=14). Among 2 the different population survey, jackal density was also found more in howling survey (1.85 per km2) followed by 2 2 sighting survey (0.46 per km2) and in active den survey (0.29 per km2). In sighting survey, from all areas sampled, the species was sighted. Highest number of individuals in total was sighted in tea gardens (n=8) followed equally by reserve forest (n=7) and unprotected forest (n=7).